2012
DOI: 10.5455/ijavms.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary energy levels on the growth performance of Kamori goat kids

Abstract: Study was conducted to evaluate the effect of different energy rations on their growth performance and carcass characteristics in Kamori goat kids. Kids were grouped into A, B and C groups each consisting of 6 kids. Group A (Control) was fed Medium energy (ME) 2.37 Mcal/kg, group B were fed High Energy (HE) 2.56 Mcal/kg, and group C was fed Low Energy (LE) 2.18 McCall/kg ration for 60 days. Average live weight gain and average daily gain was significantly higher (P<0.05) in group B whereas daily feed intake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In contrast, the depression in feed conversion with calves fed restricted ration (T4) could be attributed to the higher CF content and lower digestibility of OM than those fed the other restricted rations and control one. These findings are in agreement with those obtained by Sayed (2009), Gaafar et al (2009), Neto et al (2011, Adeleye et al (2011), Abbasi et al (2012) and Malisetty et al (2014), who concluded that feed conversion improved with increasing energy level in the diets. Results here are in contrary with those obtained by Sami et al (2016) who found that Najdi lambs fed restricted ration (20% of control ration) significantly (P<0.05) higher than those fed restricted ration (40% of control group), but no significant different with lambs fed ad libtium (control ration).…”
Section: Productive Performancesupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the depression in feed conversion with calves fed restricted ration (T4) could be attributed to the higher CF content and lower digestibility of OM than those fed the other restricted rations and control one. These findings are in agreement with those obtained by Sayed (2009), Gaafar et al (2009), Neto et al (2011, Adeleye et al (2011), Abbasi et al (2012) and Malisetty et al (2014), who concluded that feed conversion improved with increasing energy level in the diets. Results here are in contrary with those obtained by Sami et al (2016) who found that Najdi lambs fed restricted ration (20% of control ration) significantly (P<0.05) higher than those fed restricted ration (40% of control group), but no significant different with lambs fed ad libtium (control ration).…”
Section: Productive Performancesupporting
confidence: 93%
“…Moreover, Similar trend was observed with increasing the level of energy in the diets with heifer diets (Gaafar et al, 2009 andNeto et al, 2011), with growing lambs (Sowande et al, 2012, Malisetty et al, 2014, Abouheif et al, 2013and Ali et al, 2014. In contrary, some workers indicated that feed intake was inversely related to level of energy in the diet (Hossain et al, 2003, Yagoub and Babiker, 2008and Abbasi et al, 2012. Also, Sayed et al (2009) indicated that feed intake was lower with lambs fed medium or higher energy rations than those fed on low energy ration.…”
Section: Productive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Sayed found that decreasing the dietary digestible energy from 14.7 to 12.2 MJ/kg resulted in a reduced average daily gain and an increased daily feed intake in lambs fed a diet containing 14.7% protein [24]. Abbasi et al also found that lowered dietary energy level (9.1 vs. 10.7 MJ ME/kg) reduced the average daily gain and increased the feed conversion ratio in Kamori Goat Kids [25]. Our previous study [1] focused on 20-60-day-old Hu sheep lambs also found that low energy or protein diet restrained growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Other publication found that the TDN and CP ratio 5 provide better weight gain than 4. 10 The smaller ratio between TDN and CP means that the higher content of CP in the diet. Dietary protein in the rumen will be degraded by the rumen microbial enzymes to produce ammonia.…”
Section: Resultsmentioning
confidence: 99%